1998
DOI: 10.1086/305461
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength Observations of a Dramatic High‐Energy Flare in the Blazar 3C 279

Abstract: The blazar 3C 279, one of the brightest identified extragalactic objects in the γ-ray sky, underwent a large (factor of ∼10 in amplitude) flare in γ-rays towards the end of a 3-week pointing by CGRO, in 1996 January-February. The flare peak represents the highest γ-ray intensity ever recorded for this object. During the high state, extremely rapid γ-ray variability was seen, including an increase of a factor of 2.6 in ∼8 hr, which strengthens the case for relativistic beaming. Coordinated multifrequency observ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
187
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 206 publications
(200 citation statements)
references
References 28 publications
12
187
1
Order By: Relevance
“…It displays violent multiwavelength flux variability and is well studied by various observation programs (e.g. Maraschi et al 1994;Wehrle et al 1998;Lindfors et al 2006, Collmar et al 2007. Flux variability at X-rays, R band and 14.5 GHz frequency band have been found to be significantly correlated, suggesting a possible co-spatial origin.…”
Section: C 279mentioning
confidence: 99%
“…It displays violent multiwavelength flux variability and is well studied by various observation programs (e.g. Maraschi et al 1994;Wehrle et al 1998;Lindfors et al 2006, Collmar et al 2007. Flux variability at X-rays, R band and 14.5 GHz frequency band have been found to be significantly correlated, suggesting a possible co-spatial origin.…”
Section: C 279mentioning
confidence: 99%
“…The solid line is a sum of all the contributions. Simultaneous data are from Wehrle et al (1998). on organized campaigns with wide multiwavelength coverage (1993 and 1996 preÑare and Ñare).…”
Section: Multiepoch Sedsmentioning
confidence: 99%
“…1996.ÈThroughout this second multiwavelength campaign, 3C 279 was in a high state, similar to that of 1991 ; during the observation there was an extraordinary Ñare lasting 2È3 days, particularly intense in the c-ray band. Following Wehrle et al (1998), we divided the light curve in two parts, averaging the observed Ñuxes in the period January 24È28 preceding the Ñare, and in a 2 day window centered on the c-ray peak. The resulting SEDs are shown in Figure 4.…”
Section: èThe ðRst Detection Of C-ray Emission Dates From 1991mentioning
confidence: 99%
“…In part, the SSC process may be important in the soft/mid-energy X-ray bands (Inoue & Takahara 1996 ;Kubo et al 1998). Furthermore, X-ray variability usually shows lower amplitude than variability in the c-ray band (Sambruna 1997 ;Wehrle et al 1998). This suggests that X-rays produced Vol.…”
Section: Introductionmentioning
confidence: 99%